Late hematoma: a rare complication on breast implant - Pedroza, Luis Tamez; Luna, Francisco Palacious; Vargas, Iram Gonzalez (International Journal of Research in Medical Sciences, 2020)
Late hematoma is a rare complication on the use of breast implants but on recent year’s case reports become more frequent, there’s no data regarding the incidence, authors report multiple theory’s about etiology. In this case report we report a patient who presented a spontaneous late hematoma, patient arrived at doctor’s office complaining about gradual increase over the last 15 days of left breast, we treated the hematoma with guided-ultrasound drainage with total improvement of the symptoms, 1 week later the patient returns for the same symptoms that occurred the first time, an ultrasound-guided drainage is performed again and it is decided to schedule the surgical date in 1 week, as reported on previous cases we tried non-invasive management with ultrasound guided drainage on 2 attempts but patient hematoma recurred and we decided to perform drainage, capsulectomy and implant replacement, we follow the patient through the outpatient clinic 7 months later, and she has not presented a hematoma recurrence.